2018
DOI: 10.1074/mcp.tir118.000853
|View full text |Cite
|
Sign up to set email alerts
|

A Novel LC System Embeds Analytes in Pre-formed Gradients for Rapid, Ultra-robust Proteomics

Abstract: Because of low throughput and limited robustness, nano-scale liquid chromatography has been a bottleneck for advancing proteomics in biomedical research. Here, we developed and evaluated two new LC concepts—“pre-formed gradients” and “offset gradients for peptide re-focusing”—that are both implemented in the Evosep One instrument. We evaluated robustness with more than 2000 HeLa runs, demonstrated absence of cross-contamination with crude plasma samples, high proteome coverage by fractionated HeLa and routinel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
319
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(360 citation statements)
references
References 34 publications
4
319
0
Order By: Relevance
“…Technological advancements in instrumentation, coupling to mass spectrometer and improvements in separation performance have accompanied this development . Even though nanoLC–MS is still the most commonly used analysis platform for advanced proteomics , several studies have demonstrated that combination of nanoLC–MS and CE–MS methods increase the number of identified proteins as they are orthogonal and provide complementary results .…”
Section: Introductionmentioning
confidence: 99%
“…Technological advancements in instrumentation, coupling to mass spectrometer and improvements in separation performance have accompanied this development . Even though nanoLC–MS is still the most commonly used analysis platform for advanced proteomics , several studies have demonstrated that combination of nanoLC–MS and CE–MS methods increase the number of identified proteins as they are orthogonal and provide complementary results .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Evosep One system was described and applied to the analysis of offline-fractionated peptides on a Q-Exactive HF-X MS system 9 of MS utilization metric that is the same as the 'injection efficiency' value calculated by the authors of the above study revealed that the Evosep system substantially outperformed the standard Easy nanoLC system (88% vs. 52% injection efficiency). However, examination of MS1 chromatograms and MS2 scan triggering revealed the presence of extended empty elution windows in the early fractions in the set for either system ( Figure S2a-d), as described previously 14 .…”
Section: High-flow Nano-chromatography Columns Facilitate Rapid Analymentioning
confidence: 96%
“…Many improvements to sample throughput are centered on the recent popularization of microflow LC–MS/MS for both targeted and untargeted proteomics. Microflow LC–MS/MS allows for shorter gradients, quicker column washing, and equilibration, as well as better retention time stability and robustness compared to nanoflow LC–MS . Particularly interesting, a novel LC system utilizes automated offline SPE/desalting and preformed gradients at microflow flow rates for extremely robust and high throughput chromatography suitable for clinical applications …”
Section: Role Of Emerging Technologies In Advancing Biomarker Discovementioning
confidence: 99%